Le XIXe siècle à l'épreuve de la collection - Preiss, Nathalie (EPURE, Éditions et presses universitaires de Reims, 2018)
Much has been written, and very well written, on the collection in the 19th century in and through fiction: it is therefore another path that the voices gathered here would like to explore. Based on collections of all kinds (private and public, literary, historical and artistic, editorial and museological), from a necessarily and resolutely interdisciplinary perspective, the aim is to question the specificity of the act and of the discourse of the collection in the 19th century, and to think of it as a figuration and a fiction, a production and a projection of a, or even of the, 19th century.